ОПТИМІЗАЦІЯ ВМІСТУ ФІТОГОРМОНІВ У БІОПРЕПАРАРАТІ КОМПЛЕКСНОЇ ДІЇ РИЗОГУМІНІ - Комок , М.С.; Дімова , С.Б.; Волкогон , В.В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2011)
By application of the ELISA method the content of indolylacetic acid and cytokinins in the extracts of vermicompost and bacterial suspension of Bradyrhizobium japonicum M 8 (components of complex biopreparation Rhizohumin) was determined. Basing on the data obtained in the greenhouse experiments with soybean plants, the recommendations for content of these phytohormones in the preparation optimization was done.